2014
DOI: 10.1097/pas.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Human Papillomavirus–infected Immature Metaplastic Cells and Cervical Neoplasia

Abstract: Persistent cervical high-risk human papillomavirus (HR-HPV) infection results in high-grade cervical intraepithelial neoplasia (CIN2/3) and cervical carcinoma. The susceptibility of the cervix to HPV carcinogenesis and the importance of HPV18 in cervical carcinoma despite relative infrequency in CIN2/3 could be linked to HR-HPV infection of immature metaplasia (IM) at the squamocolumnar junction. Atypical IM (AIM) is an equivocal category used to describe changes in IM suggestive of high-grade neoplasia, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 5 publications
4
20
0
1
Order By: Relevance
“…In our experience, nearly all glands underneath the metaplastic and dysplastic squamous epithelium of the TZ and the adjacent columnar epithelium consistently stain positive for CK7, while the original squamous epithelium of the cervix is negative for CK7 (Dako CK7 Clone OV‐TL 12/30). Similar results were described by van der Marel et al . We therefore challenge the statement that CK7 is a SCJ marker and that only HR‐HPV infected CK7 positive SCJ cells give rise to primary HSIL/invasive cervical cancer or recurrent HSIL/invasive cervical cancer after LEEP treatment.…”
supporting
confidence: 86%
“…In our experience, nearly all glands underneath the metaplastic and dysplastic squamous epithelium of the TZ and the adjacent columnar epithelium consistently stain positive for CK7, while the original squamous epithelium of the cervix is negative for CK7 (Dako CK7 Clone OV‐TL 12/30). Similar results were described by van der Marel et al . We therefore challenge the statement that CK7 is a SCJ marker and that only HR‐HPV infected CK7 positive SCJ cells give rise to primary HSIL/invasive cervical cancer or recurrent HSIL/invasive cervical cancer after LEEP treatment.…”
supporting
confidence: 86%
“…The high prevalence of HPV-18 in CADC and its importance in ADC-CX may be related to the finding that HPV-18 is often located in the zone of immature metaplasia in the cervix, where cells have the potential for differentiation into both glandular and squamous epithelium. 33 The importance of HPV-16 and 218 has been supported by Dahlstrom's study, which found that both were detectable up to 14 years before a diagnosis of cervical adenocarcinoma. 34 HPV-52 and 245 were found in much lower proportions (5.61%, 3.92%), and HPV-59/31/58 were relatively rare (1.87-2.24%).…”
Section: Discussionmentioning
confidence: 95%
“…[11][12][13][14] The value of p16 in the diagnostic process is important, because it is detected in almost all HSIL/CIN2-3, whereas reactive mimickers, such as immature metaplasia or atrophy, are negative or show focal staining. 5,13,15 Thus, p16 staining has achieved a major role in indisputably classifying a lesion as HSIL/CIN2-3 or as reactive. 5,13,15 In contrast with the almost constantly positive results of HSIL/CIN2-3 the results of p16 staining in LSIL/CIN1 vary greatly, with some lesions being completely negative or showing focal staining, whereas others show a diffuse, basal, positive reaction.…”
mentioning
confidence: 99%
“…5,13,15 Thus, p16 staining has achieved a major role in indisputably classifying a lesion as HSIL/CIN2-3 or as reactive. 5,13,15 In contrast with the almost constantly positive results of HSIL/CIN2-3 the results of p16 staining in LSIL/CIN1 vary greatly, with some lesions being completely negative or showing focal staining, whereas others show a diffuse, basal, positive reaction. 5,11 This variability in staining has raised the question as to whether p16 overexpression in patients with LSIL/CIN1 could be correlated with the potential of 'progression'.…”
mentioning
confidence: 99%